The Relationship between the Level of Family Knowledge about Post-Stroke Care and the Level of Independence in Activity Daily Living (ADL) - Lestarini, Putu Ayu; Murianto, I Nyoman; Solehah, Eka Lutfiatus (CV. Global Health Science Group, 2024)
Stroke is a condition characterized by the rapid development of clinical signs of focal and general neurological deficits that can be severe, last for more than 24 hours, and may lead to death. Activities of Daily Living (ADL) refer to the functions and activities that an individual can normally perform without assistance from others. The level of family knowledge about post-stroke care is crucial in supporting the ADL of stroke patients. This study aims to determine the relationship between the level of family knowledge and the level of independence in ADL among post-stroke patients. This research is a descriptive correlational study with a cross-sectional design using quantitative methods. Sampling was conducted using a total sampling technique. The data collection tool used was a questionnaire. The total sample in this study was 46 people. The results showed a p-value of 0.000, which is less than the alpha value of 0.05, thus rejecting H0 and accepting Ha. This means there is a significant relationship between the level of family knowledge and ADL in post-stroke patients, with a correlation strength of 0.658, indicating a strong and positive relationship. Furthermore, the relationship between the two variables is in the same direction. If the level of family knowledge is continuously improved, the level of independence in ADL among post-stroke patients will also increase.